2020
DOI: 10.1021/acs.energyfuels.0c01183
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, Dynamics, and Rheology of Fuel Surrogates: Application of the Time–Temperature Superposition Principle in Molecular Dynamics Simulations

Abstract: All-atom molecular dynamics (MD) simulation is used to determine the thermodynamics and rheological properties of fuel surrogates, which are modeled as a mixture of n-hexadecane and methyl laurate. The volumetric properties of the studied systems, namely, density and coefficient of thermal expansion, show an excellent agreement with experiments. The temperature dependence of translational and rotational diffusion of the molecules follows an Arrhenius-type behavior, which is consistent with the temperature depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The viscosity values are plotted versus the Weissenberg number Wi = γ̇τ R , where γ̇ is the shear rate and τ R is the Rouse relaxation time of the hexadecane molecules, as seen in Figures a–d. Note that the Rouse relaxation time was obtained from τ R = ⟨ R 2 ⟩/ D , where ⟨ R 2 ⟩ and D are the square of the end-to-end distance and the diffusion coefficient of hexadecane at given temperatures for all systems, respectively …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscosity values are plotted versus the Weissenberg number Wi = γ̇τ R , where γ̇ is the shear rate and τ R is the Rouse relaxation time of the hexadecane molecules, as seen in Figures a–d. Note that the Rouse relaxation time was obtained from τ R = ⟨ R 2 ⟩/ D , where ⟨ R 2 ⟩ and D are the square of the end-to-end distance and the diffusion coefficient of hexadecane at given temperatures for all systems, respectively …”
Section: Resultsmentioning
confidence: 99%
“…The ILs (1-( n -alkyl)-3-methyl­imidazolium bistriflimide, [C n C 1 Im ] + [NTf 2 ] − ) and (1-(isoalkyl)-3-methyl­imidazolium bistriflimide, [( n – 2) m C n –1C 1 Im ] + [NTf 2 ] − ) were dispersed in hexadecane as the base oil (see Table for the chemical structures of the cations and anions). Hexadecane is a conventional oil that is often used as a reference for fuel mixtures. , The number of hexadecane molecules in the mixture was kept at 1024, while ion pairs were added to obtain IL mole fractions of 0.02, 0.05, 0.1, and 0.2 accordingly, as provided in Table . These IL contents were selected to study the thermo-rheological properties of the mixture at low and high contents when ILs can be considered as “additives” in the base oil.…”
Section: Simulation Details and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…where d = 3 is the space dimension of the considered system. Besides, in the case of MD simulations with periodic boundary conditions, it was found that the final value of diffusion coefficient, D, needs to be corrected by following term [61] which takes into account the size of the box and the shear viscosity. It reads:…”
Section: Mass Diffusivitymentioning
confidence: 99%
“…TTS can also be used in simulations to address the challenge. Prior works have shown the applicability of TTS in MD studies (both atomistic and coarse-grained) of alkanes, cross-linked epoxy networks, , dynamic covalent networks such as vitrimers, functionalized polyethylenes, asphalt, fuel surrogates, and ionic liquids (IL) . In particular, Balogun et al studied the volumetric, dynamic, and rheological properties of ILs, and using the TTS principle, they accessed the full spectrum of the rheological behavior of the IL system.…”
Section: Introductionmentioning
confidence: 99%